Planet of microbes : the perils and potential of Earth's essential life forms - Anton, Ted (The University of Chicago Press, 2017)
This book takes readers into the latest discoveries about early microbial life, where findings from the earth's furthest extremes are seeking to reshape the future of our planet and ourselves. As scientists take the next step in applying the lessons of popular and controversial research, the world's tiniest, and sometimes most dangerous, microorganisms are being tapped as allies in achieving better health and sustainable energy, while revealing fundamental clues to the mystery of where we came from. --Provided by publisher.